Nociceptive phenotype alterations of dorsal root ganglia neurons innervating the subchondral bone in osteoarthritic rat knee joints. Issue 9 (September 2016) - Aso, K.; Izumi, M.; Sugimura, N.; Okanoue, Y.; Ushida, T.; Ikeuchi, M.
Summary: Objective: Subchondral bone plays a role in generating knee joint pain in osteoarthritis (OA). The objective of this study was to clarify nociceptive phenotype alterations of subchondral bone afferents of the distal femur in mono-iodoacetate (MIA)-induced OA rats. Methods: OA was induced by intra-articular injection of MIA in rats. Two different retrograde tracers were separately injected into the knee joint cavity and the subchondral bone to identify joint and subchondral bone afferents. Immunohistochemistry was used at 2 weeks (early stage) and 6 weeks (advanced stage) after MIA injection to determine the expression of nociceptive markers (calcitonin gene-related peptide (CGRP) and tyrosine receptor kinase A (TrkA)) and the soma size distribution of CGRP-immunoreactive (IR) neurons. Histological subchondral bone and cartilage damage was scored according to the Osteoarthritis Research Society International grading system. Pain-related behavior was evaluated using weight distribution and mechanical sensitivity of the hind paw. Results: OA caused an up-regulation of CGRP, TrkA and enlargement of soma size of CGRP-IR neurons in both joint and subchondral bone afferents. CGRP and TrkA expression in subchondral bone afferents gradually increased over 6 weeks. Furthermore, up-regulation of CGRP and TrkA in subchondral bone afferents displayed a strong correlation with the subchondral bone damage score. Conclusion: Up-regulation of nociceptive markers in subchondral bone afferents correlated with subchondral bone damage, suggesting that subchondral bone is a therapeutic target, especially in the case of advanced stage knee OA. In particular, CGRP and TrkA are potentially molecular therapeutic targets to treat joint pain associated with subchondral lesions.